1985
DOI: 10.1007/bf02277447
|View full text |Cite
|
Sign up to set email alerts
|

Some features of the ozone climatology of Ontario, Canada and possible contributions of stratospheric ozone to surface concentrations

Abstract: SummaryBackground ozone concentration displayed distinct seasonal variations at all stations, with a maximum of about 40 ppb in spring and a minimum of about 23 ppb in autumn. The monthly and yearly mean diurnal variations of ozone at urban stations exhibited bi-modal characteristics not evident at rural sites. Two daily maxima and minima were recorded at urban stations, but only one maximum and one minimum at rural sites. The second minimum in the evening at urban stations was shown to be related to high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Numerous hours and days with O 3 concentrations greater than 82 ppb were experienced throughout southwestern Ontario, with stations along the shores of lakes Erie and Huron recording the highest numbers. This is likely a result of O 3 -rich plumes moving across the lakes and downward mixing at the lake shores 12 (Mukammal et al 1985). Stations in central Ontario showed fewer hours and days with O 3 concentrations greater than 82 ppb, although sites within and close to Toronto showed an elevation in the number of hours and days (Figure 7).…”
Section: Hours and Days Exceeding The Maximum Acceptable Ozone Objective Of 82 Ppbmentioning
confidence: 99%
“…Numerous hours and days with O 3 concentrations greater than 82 ppb were experienced throughout southwestern Ontario, with stations along the shores of lakes Erie and Huron recording the highest numbers. This is likely a result of O 3 -rich plumes moving across the lakes and downward mixing at the lake shores 12 (Mukammal et al 1985). Stations in central Ontario showed fewer hours and days with O 3 concentrations greater than 82 ppb, although sites within and close to Toronto showed an elevation in the number of hours and days (Figure 7).…”
Section: Hours and Days Exceeding The Maximum Acceptable Ozone Objective Of 82 Ppbmentioning
confidence: 99%
“…Some of this early work (e.g., Yap et al, 1988) suggested that local impacts on ozone levels were generally small, while some noted a more significant impact (Mukammal et al, 1982(Mukammal et al, , 1985. Ozone concentration increases of 30 ppbv over the course of a few minutes were linked through surface station and satellite observations to the passage of a lake-breeze front in a later, more detailed analysis (Hastie et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Stratospheric intrusions have long been linked to short‐lived increases in surface O 3 [ Chung and Dann , 1985; Haagenson et al , 1981; Mukammal et al , 1985; Viezee et al , 1983], particularly at higher elevations [ Ambrose et al , 2011; Davies and Schuepbach , 1994; Langford et al , 2009a; Stohl et al , 2000]. The importance of STT as a source for surface O 3 remains highly uncertain, however.…”
Section: Introductionmentioning
confidence: 99%